Utilization of Can Waste as PAC Coagulant and Alum to Remove Turbidity - Euis Nurul Hidayah; Anarta Cahyadiatma (Nusantara Science and Technology Proceedings, 2023)
Aluminum is an inorganic material that cannot be decomposed naturally in nature, while its presence in our lives is very abundant and quite crucial. One of its uses is as a raw material for food or drink cans. In the United States alone in 2012 around 38.2 billion cans of food or drink were produced. Therefore, efforts are needed to reduce aluminum waste. One use that can be made is by extracting the aluminum content in it to be used as raw material for alum coagulants and PAC. The aluminum that has been successfully extracted is then added with solutions that can cause polymerization and form alum and PAC coagulants. Next, the resulting synthetic coagulant was tested for its ability to reduce turbidity in laundry waste. Laundry waste itself was chosen because the waste processing is still simple, and generally, this type of waste contains suspended solids which can come from dirt attached to clothes or chemicals used in detergents. In this study, coagulation and flocculation were carried out with 500 mL of laundry waste sample taken and a synthetic coagulant dose of 100 PPM. After the coagulation-flocculation process was carried out, the sample was deposited with varying settling times of 30 minutes, 60 minutes, and 90 minutes. From the results of this research, it was found that synthetic PAC coagulant was more effective than alum in reducing turbidity in laundry waste. At the most effective deposition time, namely a deposition time variation of 30 minutes, the removal percentage was 57%.